2021
DOI: 10.1021/acsanm.1c00129
|View full text |Cite
|
Sign up to set email alerts
|

MoSe2 Nanosheets with Tuneable Optical Properties for Broadband Visible Light Photodetection

Abstract: Full exploitation of two-dimensional (2D) semiconducting MoSe2, an exciting 2D transition-metal dichalcogenide, in optoelectronics is hampered because of dearth of scalable production methods. Here, a redox-mediated green route growth of ultrathin MoSe2 nanosheets and nanocrystals is reported. At solvothermal condition, molybdenum acetate [(CH3COO–)2Mo2+]2 at (+II) oxidation state is employed as the molybdenum source for the first time to grow 2D MoSe2 of 2H phase. Edible olive oil acts as a solvent as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…As a result, we found that for MoS 2 Δ 0 = 76 ± 2 meV and Δ LO = 210 ± 24 meV, while for MoSe 2 , Δ 0 = 38.6 ± 0.2 meV and Δ LO = 39.7 ± 0.9 meV. Literature reports values of Δ 0 between 52 and 66 meV for MoS 2 (4 meV in hBN-encapsulated MoS 2 ) and 1.5–4.3 meV for MoSe 2 and values of Δ LO between 42.6 and 86 meV for MoS 2 and 11.2–15.6 meV for MoSe 2 . , This suggests that our colloidal TMD nanosheets can still be further improved; however, our MoSe 2 monolayer already exhibits a substantially narrower emission linewidth than the MoS 2 monolayer, suggesting that the latter might be more suitable for further application in optoelectronic or photonic devices. …”
Section: Resultsmentioning
confidence: 54%
“…As a result, we found that for MoS 2 Δ 0 = 76 ± 2 meV and Δ LO = 210 ± 24 meV, while for MoSe 2 , Δ 0 = 38.6 ± 0.2 meV and Δ LO = 39.7 ± 0.9 meV. Literature reports values of Δ 0 between 52 and 66 meV for MoS 2 (4 meV in hBN-encapsulated MoS 2 ) and 1.5–4.3 meV for MoSe 2 and values of Δ LO between 42.6 and 86 meV for MoS 2 and 11.2–15.6 meV for MoSe 2 . , This suggests that our colloidal TMD nanosheets can still be further improved; however, our MoSe 2 monolayer already exhibits a substantially narrower emission linewidth than the MoS 2 monolayer, suggesting that the latter might be more suitable for further application in optoelectronic or photonic devices. …”
Section: Resultsmentioning
confidence: 54%
“…The lower energy PL emission can be ascribed to the transition between quantized energy levels and the other peak is might be due to defect state mediated transition. 27,28 The PL intensity of all the composites prepared was lower than the pure MoSe 2 which indicates that the photocatalytic activity of the composites is higher as compared to individual components because of the higher separation efficiency of the photo-induced charges in the composites. 004), ( 006), ( 102), ( 111), ( 105), ( 201), ( 110), ( 103), ( 200) and (203) (hkl) planes respectively (JCPDS le no 77-1715) and intensity of these peaks increases as the amount of MoSe 2 in the composite increases.…”
Section: Resultsmentioning
confidence: 95%
“…The peaks at 235 and 281 cm −1 are related to the out-of-plane A 1g and in-plane E 2g 1 vibrational modes of MoSe 2 , respectively. 22 The peak at 195 cm −1 is attributed to the E 1g mode, which is forbidden in backscattering but appears due to the resonance effect. The peak at 336 cm −1 is connected to the 2-phonon frequency of the B 2g branch at the M point.…”
Section: Morphology and Structure Of The Synthesis Materialsmentioning
confidence: 97%